Compounds of triphenylstibine and platinum: synthesis, properties and reactivity - Barbieri, R.; Bellato, C. R.; Massabni, A. C. (Springer, 2005)
The reactivity of [Pt(SbPh3)(3)], a compound of zerovalent platinum, exceptionally stable in air, is described. The compounds [{Pt(SbPh3)(3)}(2)N-2], containing bridging dinitrogen, [{Pt(SbPh3)(3)}(2)C-2], with an ethynediyl group also bridging, and [Pt(CO)(2)(SbPh3)(2)], were all obtained under ordinary pressure of nitrogen, acetylene or carbon monoxide, respectively, and are also described. Among the products of the reactions, the dimer [PtBr3(SbPh3)(2)](2) and the mixed complexes [PtL2(SbPh3)(2)] (L = PPh3, AsPh3) were also obtained. Some of these complexes are luminescent when excited by u.v. radiation.